Assessment of the effect of new tourism products on the economic recovery of rural areas in the context of empirical research on selected communes of the Lublin Voivodeship - Szczęsna, Joanna; Wesołowska, Monika (Turyzm/Tourism, 2020)
This paper presents examples of several original tourism products available in the rural areas of the Lublin Voivodship (Eastern Poland) which in the context of empirical research have contributed to the development of tourism. The primary objective is to determine how selected tourism products are created, and their role in the development of the tourism function and local development in general. The article employs the case study method and concerns four tourism products in four communes of the Lublin Voivodeship. An assessment of the effect of the created product on local development was based on research employing a diagnostic survey in the form of a questionnaire and interviews. The interviews concerned the process of the creation of a tourism product and its effects was undertaken among entrepreneurs from the tourism industry, and the questionnaire concerning the effects of the resulting tourism product on local development was addressed to residents. The survey results showed that in each of the analysed cases, the creation of the tourism product could have considerably contributed to the development of the tourism function and economic development of rural areas where such products were created. Socio-economic phenomena accompanying the development of the tourism function are perceived as positive by residents of selected communes that see the development of tourism as a chance to improve their image and improve living conditions.